The readiness of lecturers in embedding soft skills in the bachelor's degree program in Malaysian institutes of teacher education - Hassan, Aminuddin; Maharoff, Marina; Zainal Abiddin, Norhasni (Redfame Publishing, 2014)
This is a preliminary research to obtain information to formulate a problem statement for an overall study of the embedding of soft skills in the program courses in higher learning institutions. This research was conducted in the form of single case and multi-case studies. The research data was attained through mixed methods; the quantitative method by utilizing questionnaires and the qualitative method utilizing open-ended questionnaires. Qualitative data were used as supporting data in this research. This research sought to study two main issues; the readiness of lecturers and problems encountered in embedding soft skills into teachers’ bachelor’s degree courses in the institutes of teacher education in Malaysia. Quantitative data was processed manually to show frequency, while qualitative data was processed according to themes. Research findings indicated that a majority of lecturers are interested and ready to embed soft skills in the core courses. However, lecturers lamented about problems encountered in embedding soft skills in teaching and learning of courses even though the curriculum of the programs have been designed holistically to fulfill the needs to develop soft skills within trainee teachers.